A single cell death is disruptive to spontaneous Ca2+ activity in astrocytes - Gomez-Godinez, Veronica; Li, Huayan; Kuang, Yixuan; Liu, Changchen; Shi, Linda; Berns, Michael W. (Frontiers in Cellular Neuroscience, 2022)
Astrocytes in the brain are rapidly recruited to sites of injury where they phagocytose damaged material and take up neurotransmitters and ions to avoid the spreading of damaging molecules. In this study we investigate the calcium (Ca2+) response in astrocytes to nearby cell death. To induce cell death in a nearby cell we utilized a laser nanosurgery system to photolyze a selected cell from an established astrocyte cell line (Ast1). Our results show that the lysis of a nearby cell is disruptive to surrounding cells’ Ca2+ activity. Additionally, astrocytes exhibit a Ca2+ transient in response to cell death which differs from the spontaneous oscillations occurring in astrocytes prior to cell lysis. We show that the primary source of the Ca2+ transient is the endoplasmic reticulum.